Modeling transverse micro flow in dry fiber placement preforms. (June 2020) - Rimmel, Oliver; May, David
Dry fiber placement has a large potential for manufacturing preforms for primary-load components at minimum scrap rate and fiber crimp. Yet, challenging impregnation behavior due to low permeability of these preforms during liquid composite molding imposes a need for further research to optimize preform structure for higher permeability. For full understanding of flow behavior within these preforms, flow has to be considered on micro scale (in between single fibers), on meso scale (in between single rovings or strands), and on macro scale (on scale of parts to be manufactured). While macro and meso scale can be measured in experiments or derived from filling times in real processes, micro scale is usually not easily assessable and accessible for standard textile materials. Analytical approaches are limited to regular fiber arrangements (square and hexagonal) that are strongly differing from real arrangements. The present work deals with application of a numerical solver to random fiber arrangements to determine micro permeability transverse to the fiber orientation, for later use in meso- and macro-scaled models. As a premise for reliable calculation, guidelines for boundary conditions as well as size and resolution of the representative volume element are elaborated in the course of this work. Calculated out-of-plane micro permeabilities are subsequently compared to real experiments and show good accordance. The influence of binder particles on micro permeability has not yet been conclusively clarified.